Intracellular in situ labeling of TiO(2) nanoparticles for fluorescence microscopy detection - Brown, Koshonna (Nano Res, 2017)
Titanium dioxide (TiO(2)) nanoparticles are produced for many different purposes, including development of therapeutic and diagnostic nanoparticles for cancer detection and treatment, drug delivery, induction of DNA double-strand breaks, and imaging of specific cells and subcellular structures. Currently, the use of optical microscopy, an imaging technique most accessible to biology and medical pathology, to detect TiO(2) nanoparticles in cells and tissues ex vivo is limited with low detection limits, while more sensitive imaging methods (transmission electron microscopy, X-ray fluorescence microscopy, etc.) have low throughput and technical and operational complications. Herein, we describe two in situ post-treatment labeling approaches to stain TiO(2) nanoparticles taken up by the cells. The first approach utilizes fluorescent biotin and fluorescent streptavidin to label the nanoparticles before and after cellular uptake; the second approach is based on the copper-catalyzed azide-alkyne cycloaddition, the so-called Click chemistry, for labeling and detection of azide-conjugated TiO(2) nanoparticles with alkyne-conjugated fluorescent dyes such as Alexa Fluor 488. To confirm that optical fluorescence signals of these nanoparticles match the distribution of the Ti element, we used synchrotron X-ray fluorescence microscopy (XFM) at the Advanced Photon Source at Argonne National Laboratory. Titanium-specific XFM showed excellent overlap with the location of optical fluorescence detected by confocal microscopy. Therefore, future experiments with TiO(2) nanoparticles may safely rely on confocal microscopy after in situ nanoparticle labeling using approaches described here.